2020
DOI: 10.1002/oby.22940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 Pandemic on Unhealthy Eating in Populations with Obesity

Abstract: Objective This study aimed to examine the impact of the coronavirus disease (COVID‐19) pandemic on patronage to unhealthy eating establishments in populations with obesity. Methods Anonymized movement data accounting for roughly 10% of devices in the United States at 138,989 unhealthy eating locations from December 1, 2019, through April 2020 and the percentage of adults with obesity, the poverty rate, and the food environment index in 65% of United States counties were collected and merged. A cluster correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 8 publications
3
55
1
2
Order By: Relevance
“…These figures are slightly more in line with our findings than those of the Italian, Canadian and Polish study findings. Nevertheless, our observation that the lockdown was more likely to take a toll on healthy dietary choices of participants with obesity has been observed in a variety of international studies ( Ashby, 2020 ; Di Renzo et al, 2020 ; Sidor & Rzymski, 2020 ). All together these findings suggest that different lockdown strategies implemented in different countries have influenced eating behaviors differently.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These figures are slightly more in line with our findings than those of the Italian, Canadian and Polish study findings. Nevertheless, our observation that the lockdown was more likely to take a toll on healthy dietary choices of participants with obesity has been observed in a variety of international studies ( Ashby, 2020 ; Di Renzo et al, 2020 ; Sidor & Rzymski, 2020 ). All together these findings suggest that different lockdown strategies implemented in different countries have influenced eating behaviors differently.…”
Section: Discussionmentioning
confidence: 52%
“…due to snacking in response to food cues, stress or little sleep) ( Zachary et al, 2020 ) and in younger adults ( Sidor & Rzymski, 2020 ), increased consumption of unhealthy food, uncontrolled eating, snacking between meals and overall higher number of main meals ( Ammar et al, 2020 ; Carroll et al, 2020 ; Sidor & Rzymski, 2020 ). Furthermore, it was observed that having a higher Body Mass Index (BMI) and lower age were associated with an increase in junk food consumption ( Ashby, 2020 ; Di Renzo et al, 2020 ; Sidor & Rzymski, 2020 ) and that children with obesity increased their snack intake and sugary drinks during lockdown ( Pietrobelli et al, 2020 ). In contrast, a Spanish study indicated that the lockdown measures led to the adoption of a healthier diet in an adult study population ( Rodríguez-Pérez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that the psychological effects of lockdown (increased anxiety, stress, frustration, confusion, anger, and boredom) and the deviation from usual routines would result in overeating of unhealthy foods, which in turn may exacerbate overweight and increase the risk of cardiovascular and metabolic disorders (Bhutani and Cooper 2020;Martinez-Ferran et al 2020;Mattioli et al 2020). Binge eating due to the lockdown, particularly among those already experiencing disordered eating and obesity, appears to have increased health inequities in the United States and Australia (Ashby 2020;Phillipou et al 2020). However, home cooking is generally considered to be 'healthier' than eating out.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, negative associations between stress and intakes of fresh fruits and vegetables have been demonstrated [30][31][32][33]. Early research during the COVID-19 pandemic suggests changes in dietary behavior and food choices [34,35]: consumption of pasta, flour, and frozen food has increased, while consumption of fresh foods has decreased [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%